2019
DOI: 10.1007/s10995-019-02824-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hurricanes Irma and Maria on Puerto Rico Maternal and Child Health Research Programs

Abstract: Puerto Rico was hit by two major hurricanes in September 2017 causing great devastation, losing over 90% of the power grid, wireless communication and access to potable water, and destroying many homes. Our research programs: Puerto Rico Testsite for Exploring Contamination Threats (PROTECT), Center for Research on Early Childhood Exposure and Development in Puerto Rico (CRECE), Zika in Infants and Pregnancy (ZIP), and Environmental Influences on Child Health Outcomes (ECHO) are ongoing observational cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…One aspect was securing transportation to pharmacies and clinics due to loss of public transit. Further, many pharmacies were closed due to lack of electricity and those pharmacies that were open usually lacked internet access to verify prescriptions [21]. Despite that, all our participants received the care they needed; in the advent of Hurricane Maria, access to health was one of the main concerns of the participants of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect was securing transportation to pharmacies and clinics due to loss of public transit. Further, many pharmacies were closed due to lack of electricity and those pharmacies that were open usually lacked internet access to verify prescriptions [21]. Despite that, all our participants received the care they needed; in the advent of Hurricane Maria, access to health was one of the main concerns of the participants of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Access to adequate perinatal care following a natural disaster can be a challenge for new and expecting mothers. Women are more likely than men to receive inadequate health care following a natural disaster and the consequences are more severe for pregnant women due to the needs of the developing fetus [21][22][23]. A study that observed the impact of Hurricane Irma and Maria on Maternal and Child Research Programs explains how access to continued health care was a major issue in the wake of both hurricanes.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and intensity of extreme weather events such as hurricanes and floods are expected to increase. Hurricanes reduce access to safe food and water, and induce stress by disruption of existing infrastructures [71][72][73][74]. During a hurricane, pregnant women report significant fear of losing home and/or job, and serious concerns about the health of their baby and the birth process [75][76][77].…”
Section: Extreme Weather Eventsmentioning
confidence: 99%
“…Thus, individual, community and state responsibilities in terms of access to resources need be addressed during emergency preparedness. For example, in PROTECT we have provided participants, after consulting them, with materials like water filters, mosquito nets, powdered milk, and baby products, as well as educational material related to emergency preparedness aimed at pregnant and post-partum women (i.e., infographics from CDC and local authorities, materials developed by the PROTECT team) [ 33 ]. In addition, state and local agencies and institutions must work on emergency preparedness that responds to the specific needs of diverse communities and populations such as pregnant and post-partum women and provides them with access to resources [ 18 , 34 ].…”
Section: Discussionmentioning
confidence: 99%